2022
DOI: 10.1007/s11255-022-03366-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative endogenous testosterone density predicts disease progression from localized impalpable prostate cancer presenting with PSA levels elevated up to 10 ng/mL

Abstract: Objective To investigate endogenous testosterone density (ETD) predicting disease progression from clinically localized impalpable prostate cancer (PCa) presenting with prostate-specific antigen (PSA) levels elevated up to 10 ng/mL and treated with radical prostatectomy. Materials and methods In a period ranging from November 2014 to December 2019, 805 consecutive PCa patients who were not under androgen blockade had endogenous testosterone (ET, ng/dL) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Dr. Porcaro and collegues form Italy performed in page 450 ( 5 ) a nice study about prognostic impact of the 2012 Briganti nomogram on prostate cancer (PCa) progression in intermediate-risk (IR) patients presenting with PSA <10ng/mL, ISUP grade group 3, and clinical stage up to cT2b treated with robot assisted radical prostatectomy eventually associated with extended pelvic lymph node dissection and concluded that in IR PCa patients with PSA <10ng/mL, ISUP grade group 3, and clinical stage up to cT2b, the 2012 Briganti nomogram independently predicts PCa progression. In this challenging subset of patients, this tool can identify prognostic subgroups, independently by upgrading issues.…”
mentioning
confidence: 99%
“…Dr. Porcaro and collegues form Italy performed in page 450 ( 5 ) a nice study about prognostic impact of the 2012 Briganti nomogram on prostate cancer (PCa) progression in intermediate-risk (IR) patients presenting with PSA <10ng/mL, ISUP grade group 3, and clinical stage up to cT2b treated with robot assisted radical prostatectomy eventually associated with extended pelvic lymph node dissection and concluded that in IR PCa patients with PSA <10ng/mL, ISUP grade group 3, and clinical stage up to cT2b, the 2012 Briganti nomogram independently predicts PCa progression. In this challenging subset of patients, this tool can identify prognostic subgroups, independently by upgrading issues.…”
mentioning
confidence: 99%